Analisis Pengambilan Keputusan Dalam Kondisi Pasti Pada Manajemen Pendidikan - Sapri Ramadhani; Leni Hafsary; Nasya Putri (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2025)
Decision-making under conditions of certainty is a crucial component in educational management, as it allows school leaders and staff to take actions based on complete, accurate, and predictable information. This study aims to explain the fundamental concept of certainty-based decision-making, describe its application within school management, and analyze how structured procedures, data validity, and regulatory alignment support the creation of effective decisions. Using a literature review method, this research examines how deterministic decisions operate in administrative, instructional, and organizational contexts. The analysis reveals that certainty-based decision-making enables schools to streamline administrative processes, maintain policy consistency, optimize resource allocation, and improve overall institutional performance. Findings also show that the success of this decision-making model depends on the availability of reliable data, the readiness of human resources, and the support of digital management systems. The study concludes that when applied systematically, decision-making under conditions of certainty becomes an essential instrument for enhancing stability, accountability, and efficiency in educational governance. The results provide both theoretical contributions and practical insights for strengthening managerial practices in schools